One new genus and six new species (Orthoptera: Tettigoniidae: Meconematini) from Yunnan, China - Shi, Fuming; Zhang, Lidan (Zootaxa, 2021)
The paper reported one new genus and six new species from Yunnan, China. The new genus, Neoteratura gen. nov. is similar to the genus Alloteratura Hebard, 1922, but differs from the latter by: apical segment of maxillary palpus slightly shorter than subapical one; humeral sinus indistinct; tegmina shorter, not reaching or slightly surpassing apex of abdomen, but longer than hind wings; male genitalia sclerotized, simple; cercus divided into two branches, or with branches. It resembles the genus Borneratura Gorochov, 2008, but differs from the latter by: tegmina and hind wings shorter; male genitalia sclerotized, cercus with branches.